Report of a Father With Congenital Bilateral Absence of the Vas Deferens Fathering a Child With Beare–Stevenson Syndrome - Ferreira, Leonardo C.; Dantas Junior, José H. (Frontiers in Genetics, 2020)
Background: Apert, Pfeifer and Crouzon syndromes are autosomal dominant diseases characterized by craniosynostosis. They are paternal age effect disorders. The association of paternal age with the Beare-Stevenson syndrome (BSS), one of the most rare and severe craniosynostosis, has been uncertain. Gain-of-function mutations in FGFR2 have been described as the cause for these syndromes, which arise in the male germline evolving through a mechanism involving spermatogonial clonal expansion. Case report: Here we describe a child affected with BSS, whose father was 36 years old and had Congenital Bilateral Absence of the Vas Deferens (CBAVD). The child was heterozygous for the pathogenic variant FGFR2 p.Tyr375Cys. By reviewing the literature, we found BSS fathers are older than BSS mothers (mean age in years: 39 ±10 vs 30 ±6, p=0.006). Male age greater than 34 years and CBAVD are both factors associated with poor spermogram parameters, which may represent an additional selective pressure to sperm carrying FGFR2 gain-of-function mutations. Conclusion: These findings are consistent with the hypothesis that BSS is a paternal-origin genetic disorder. Further experimental studies would be needed to confirm this hypothesis.